Non-market strategy as a framework for exploring commercial involvement in health policy: A primer. (October 2020) - Eastmure, Elizabeth; Cummins, Steven; Sparks, Leigh
Abstract: This paper outlines the role of non-market strategy and its relevance to public health. Three broad categories of non-market activity are described: corporate political activity, Corporate Social Responsibility (CSR) and legal activity, with examples relevant to public health. The importance to public health researchers of considering business activity through a non-market lens has been outlined. Using a non-market strategy perspective can assist with understanding the commercial determinants of health and analysing the writing of the 'rules of the game'. Highlights: Businesses use non-market strategies to influence public health policy. Non-market strategy can include political, social responsibility and legal activity. Non-market strategy can enhance understanding of commercial determinants of health. Analysis of non-market strategies can be undertaken with publicly available data.